Training in competencies for professional performance in public relations: A comparison between Ecuador and Spain - Cisternas Osorio, Rodrigo Ernesto; Baquerizo-Neira, Gabriela; Cordero Redondo, Adrián; Fernández-Hernández, Ruth; Álvarez-Nobell, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Different studies maintain that the profile of the public relations professional varies according to the countries and regions, due, among other reasons, to the academic development and the dynamics of the professional market. This research comparatively analyses, at a theoretical level (definition of competencies and regulatory frameworks) and empirically (academic programs and trends), the main academic offer for degrees in the cases of Ecuador and Spain, based on the following dimensions: development of competencies, performance areas and graduate profiles. The professional profile of public relations is demanding new skills and abilities that in many cases go beyond the traditional work of the area.